Pentingnya Laporan Keuangan dalam Menilai Kinerja Keuangan - Ahmad Hafizi; Joni Hendra; Selvi Darma Yanti; Suratin Suratin; Yulfi Hartati (BADAN PENERBIT STIEPARI PRESS, 2025)
In the current era, the development of technology is very rapid and increasingly sophisticated, it is used to find out financial statements in companies. The purpose of this study is to assess the company. This analysis has benefits for the company as input on the importance of financial reports in terms of assessing the performance of a company to make decisions in the future or in the future. For analysts, it can be useful to find out statements about company performance. This analysis generally uses a literature review method with descriptive quantitative data. The data source for this analysis is from secondary data, namely indirect data sources through literature, notes, and existing books. Performance is financial performance which is a description of the financial condition of a company in a certain period both in terms of raising funds and channeling funds, which is measured by the indicators of capital adequacy, liquidity and profitability. The advantages of the importance of performance appraisal for management are to manage organizational operations, assist decision making, identify employee training and development needs, provide feedback to employees how leaders reward their performance, provide a basis for award distribution to employees